2007
DOI: 10.1093/annonc/mdm206
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of circulating epithelial tumor cells (CETC) for therapy monitoring during neoadjuvant (primary systemic) chemotherapy in breast cancer

Abstract: Background: Having demonstrated in a previous report that the response of circulating epithelial tumor cells (CETC) during the first cycles of primary (neoadjuvant) chemotherapy perfectly reflects the response of the tumor, in the present study the changes in cell numbers during subsequent cycles and their possible impact on the therapy's outcome were examined. Patients and methods:In 58 breast cancer patients CETC were quantified during therapy with either EC (epirubicin/ cyclophosphamid) or dose intensifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 39 publications
6
63
2
3
Order By: Relevance
“…In 29 patients who were tested for CTCs before and after the first cycle of chemotherapy, multivariate analysis suggested that CTC count increase is an independent poor prognostic marker only for PFS (hazard ratio = 6.58, 95% confidence interval: 1.37-31.6, P=0.019) (Table IV). Our results may be partly consistent with the reports from Matsushita et al and other researchers (5,(27)(28)(29)(30). On the contrary, other studies considered changes in CTC count during the course of chemotherapy to not be predictive of clinical outcome or response to therapy (31,32).…”
Section: Progression-free Survivalsupporting
confidence: 93%
“…In 29 patients who were tested for CTCs before and after the first cycle of chemotherapy, multivariate analysis suggested that CTC count increase is an independent poor prognostic marker only for PFS (hazard ratio = 6.58, 95% confidence interval: 1.37-31.6, P=0.019) (Table IV). Our results may be partly consistent with the reports from Matsushita et al and other researchers (5,(27)(28)(29)(30). On the contrary, other studies considered changes in CTC count during the course of chemotherapy to not be predictive of clinical outcome or response to therapy (31,32).…”
Section: Progression-free Survivalsupporting
confidence: 93%
“…This seems to be particularly important in neoadjuvant therapy, where CTCs reflects the final response to tumor, already from early cycles. 13 that mutations in the p53 gene in primary breast carcinoma are not essential for hematogenous dissemination of cancer cells. These cells, deficient of p53, are susceptible of accumulating mutations and show a more resistant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, recent studies have demonstrated the potential of CTCs detection as an indicator of therapeutic success in patients with metastatic breast cancer. [12][13][14] The aim of this study was to assess the role of CTCs in peripheral blood of breast cancer patients as a proxy for tumor recurrence and patient survival. We set out a trial to explore the presence of CTCs during and after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown already in previous analyses in lung [14] and breast cancer patients [15] that increasing cell numbers after surgery are correlated with a higher risk of relapse, that patients with a good initial response to neoadjuvant treatment have improved relapse free survival [27], as well as that a stable number of CETCs can be detected without disease recurrence even after several years [8].…”
Section: Discussionmentioning
confidence: 90%